Evolution of Biotechnology and Information Technology and Its Impact on Human Security - E. S. Zinovieva; Y. I. Vojtenko (Vestnik MGIMO-Universiteta)
Abstract: The development of post-industrial society initiates profound economic, technological and cultural change in the way of life of all mankind. The revolutionary breakthroughs in the field of new technologies such as biotechnology and information technology are reflected in all spheres of human activity, directly affecting the human security. The article analyzes the consequences of widespread usage biotechnology and information technology in the foreign policy practice on the basis of the human security theory. The detailed description of the main directions of the use of biometric technology in the foreign policy and consular practices is provided, the challenges and threats to information security associated with biometrics are analyzed, arising from widespread biotechnology are the main challenges and threats to as well as human security threats arising at the present stage of development and application of these technologies. Human security threats associated with the use of biotechnology are placed in the broader context of global trends in scientific and technological development. The recommendations are formulated in the field of foreign policy and international cooperation, which would neutralize new threats to international and personal safety arising at the present stage of development of biotechnology. The authors conclude that in order to ensure ethical regulation of new technologies that address issues of human security, it is necessary to organize multi-stakeholder partnerships at national and international level with the participation of states, representatives of civil society, business and the research community.